Mangroves degradation: A local perspective on its awareness - Abd Rahman, Mazni Adibah; Asmawi, M. Zainora (Malaysian Institute of Planners, 2016)
Mangroves in Malaysia reside on the coastlines, and the largest areas of mangrove are in the Northern Sabah. Over the past decades, mangrove species have been reported to be disappearing from the globe. It is due to several natural processes that have been inserted to fill the needs of the increased population. These include illegal logging, agriculture activities and urbanisation. In this regards, awareness of the local residents about the problem of mangrove depletion is important to inhibit the problem to prolong further.Therefore, this research was conducted to determine the degree of awareness of local residents on the importance of mangroves in managing environmental quality. Consequently, a questionnaire survey was conducted on 103 respondents to examine their awareness on the subject of mangrove degradation.The respondents were selected randomly among local residents of Kuala Selangor district.It is found that only twenty percent of the total number of respondents are totallyaware of the issue and acted upon it; either taking part in the endeavours made by the government as well as those with the non-governmental bodies or practicing mangroves replanting at their backyard.